Quantitative Benefit-Risk Models Used for Rotavirus Vaccination: A Systematic Review. (12th March 2020) - Arlegui, Hugo; Nachbaur, Gaëlle; Praet, Nicolas; Bégaud, Bernard
Abstract: Background: Although rotavirus vaccines have proven to prevent the risk of rotavirus gastroenteritis (RVGE) in children under 5 years old, they are also associated with an increased transient risk of intussusception (IS). Several quantitative benefit-risk models (qBRm) are performed to measure this balance in hospitalizations and deaths prevented versus the ones induced. Method: In this study, our objective was to provide a complete overview of qBRm used for rotavirus vaccination. We systematically searched 3 medical literature databases to identify relevant articles, in English, that were published between 2006 and 2019. Results: Of the 276 publications screened, 14 studies using qBRm for rotavirus vaccination were retained, based on preselected criteria. Four were performed in low- and middle-income countries. Almost all (13 of 14) displayed the following characteristics: force of infection assumed to be constant over time (static model), indirect effect of rotavirus vaccination (herd effect) not considered, closed model (individuals not allowed to enter and/or exit the model over time), and aggregated level (no tracking of individual's behavior). Most of the models were probabilistic (9 of 14) and reported sensitivity and/or scenario analyses (12 of 14). Input parameter values varied across studies. Selected studies suggest that, depending on the models used, for every IS hospitalization and death induced, vaccination would prevent, respectively, 190–1624 and 71–743 RVGE-related hospitalizations and deaths. Conclusions: The benefits of rotavirus vaccination were shown to largely exceed the increased risk of IS, across all studies. Future research aiming to harmonize qBRm for rotavirus vaccination should ensure the comparability of studies and provide additional information for regulatory authorities, physicians, and patients.